Systemic risk factors in patients younger than 50 years with retinal vein occlusionsl: Sistemski dejavniki tveganja pri bolnikih mlajših, od 50 let, z zaporo mrežnične vene - Kuhta, Katja; Petelin, Katarina; Masten, Matejka; Košič Knez, Nina; Pahor, Dušica (Acta Medico-Biotechnica, 2022)
Purpose: To identify the etiological factors of patients with retinal vein occlusion (RVO) younger than 50 years.Methods: The clinical records of patients with RVO under the age of 50 years seen between January 2015 and December 2020 were analyzed retrospectively. Past medical history, drug use, thrombophilic features, hyperviscosity syndromes, and pathologies that may have caused vasculitis were noted. All patients underwent ocular and systemic examinations, as well as complete screening for thrombophilic risk factors.Results: A total of 20 patients (22 eyes) were recruited in the study, 14 (70%) of whom were male and seven (30%) were female. The mean age was 42 years. The diagnosis was central retinal vein occlusion (CRVO) in 12 eyes (60%) and branch retinal vein occlusion (BRVO) in 10 eyes (40%). Two patients had bilateral BRVO. Hypertension was determined in eight (38%) patients, diabetes mellitus in two (9.5%) patients, and dyslipidemia in 11 (52%) patients. Mutation of factor V Leiden was found in one (5%) patient. An ocular risk factor was pigmentary glaucoma in two (10%) patients. Other diseases that were also noted included Behcet's (5%) and Eale's disease (5%). Multiple etiological factors were detected in 10 (48%) patients. No risk factors were found in only four (19%) patients.Conclusion: Dyslipidemia was the most prevalent risk factor for RVO. Work-up for the etiology of RVO in younger patients may reveal nontraditional risk factors for retinal vein occlusion. It was particularly interesting that thrombophilic disorder was found in only one female CRVO patient. Etiological factors that might result in RVO in young individuals should therefore be investigated in detail.
Keywords: etinal vein occlusion, risk factor, dyslipidemia, thrombophylia